COVID-19 economic impact and Saudi stimulus package effectiveness / Nahla Samargandi - Samargandi, Nahla (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study examined baseline macroeconomic structure, economic impacts of the COVID-19 lockdown, and government stimulus package effectiveness to mitigate pandemic impacts in Saudi Arabia. By a disaggregated analysis, we identified the sectoral contribution in terms of intermediate, private and public demand, labour compensation and trade by utilising the Input-Output Table. By analysing the point of sales, we demonstrated hard-hit sectors by the lockdown. The Saudi economy shrank by 1% in Q1 of the fiscal year 2020 due to oil price collapse and the lockdown. The stimulus package may rebound the economy (costing external debt). We provide several policy implications.